Sacrum – profanum. Dwa żywoty misy mosiężnej z Santoka - Janowski, Andrzej; Zamelska-Monczak, Kinga (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
The article presents the results of interpretation of a part of a brass bowl unearthed in 1958 in the course of millennial excavations in Santok. An engraved ornament is visible on one of the surfaces of the sheet, the most important part of which is an outline of a bust with a head in a hat shown in profile. Three Latin characters allow to identify the image as a personification of Envy (Invidia), while the sheet itself is a fragmented, so called brass bowl representing deadly sins. The vessel were forged in Rhineland and might have been originally used for liturgical ceremonies in St. Andrew’s church and its fragmented part was uncovered in the context of a smithy as a recycled material.